(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
This article examines the impact of artificial intelligence on enterprises and the expected efficiency from it, and analyzes the impact of artificial intelligence on the economy using a neoSchumpeterian economic approach. Artificial intelligence systems